Is Perceived Discrimination in Pregnancy Prospectively Linked to Postpartum Depression? Exploring the Role of Education - Stepanikova, Irena; Kukla, Lubomir (Maternal and child health journal, 2017)
Objectives The role of perceived discrimination in postpartum depression is largely unknown. We investigate whether perceived discrimination reported in pregnancy contributes to postpartum depression, and whether its impact varies by education level. Methods Prospective data are a part of European Longitudinal Study of Pregnancy and Childhood, the Czech Republic. Surveys were collected in mid-pregnancy and at 6 months after delivery. Depression was measured using Edinburgh Postnatal Depression Scale. Generalized linear models were estimated to test the effects of perceived discrimination on postpartum depression. Results Multivariate models revealed that among women with low education, discrimination in pregnancy was prospectively associated with 2.43 times higher odds of postpartum depression (p < .01), after adjusting for antenatal depression, history of earlier depression, and socio-demographic background. In contrast, perceived discrimination was not linked to postpartum depression among women with high education. Conclusions Perceived discrimination is a risk factor for postpartum depression among women with low education. Screening for discrimination and socio-economic disadvantage during pregnancy could benefit women who are at risk for mental health problems.
Keywords: psychiatrické posuzovací škály; poporodní období; Psychiatric Status Rating Scales; deprese; Pregnancy Complications; komplikace těhotenství; těhotenství; Postpartum Period; Socioeconomic Factors; Česká republika; Depression; Perceived discrimination; průzkumy a dotazníky; percepce; Discrimination, Psychological; Prospective Studies; Adult; Depression, Postpartum; Czech Republic; poporodní deprese; socioekonomické faktory; Postpartum depression; Education; ženské pohlaví; Humans; prospektivní studie; Pregnancy; Surveys and Questionnaires; Socio-economic status; Perception; rizikové faktory; dospělí; diskriminace (psychologie); Female; Risk Factors; lidé